2020
DOI: 10.1080/17476348.2020.1739525
|View full text |Cite
|
Sign up to set email alerts
|

Role of the mucins in pathogenesis of COPD: implications for therapy

Abstract: Introduction: Evidence accumulated in the last decade has started to reveal the enormous complexity in the expression, interactions and functions of the large number of different mucins present in the different compartments of the human lower airways. This occurs both in normal subjects and in COPD patients in different clinical phases and stages of severity. Areas covered:We review the known physiological mechanisms that regulate mucin production in human lower airways of normal subjects, the changes in mucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…Surprisingly, there is an absence of controlled clinical trials concerning the impact of LAMAs on mucin synthesis, production and rheology [72], while there are conflicting findings regarding airway mucociliary clearance [28,34,73]. TAGAYA et al [28] reported that TIO reduced the nasal clearance time in COPD patients, an effect that could be the result of a lower mucus hypersecretion and an increase in mucociliary clearance time in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there is an absence of controlled clinical trials concerning the impact of LAMAs on mucin synthesis, production and rheology [72], while there are conflicting findings regarding airway mucociliary clearance [28,34,73]. TAGAYA et al [28] reported that TIO reduced the nasal clearance time in COPD patients, an effect that could be the result of a lower mucus hypersecretion and an increase in mucociliary clearance time in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activation of EGFR, also leads to goblet cell hyperplasia, mucus hypersecretion, and overproduction of MUC5AC, which may exacerbate the pathological changes in respiratory diseases ( 76 79 ). Overproduction of the MUC5AC gene is a characteristic of many respiratory diseases including CF, asthma, and COPD ( 7 , 80 , 81 ), creating hyper-concentrated mucus, which is thicker, more adherent and prone to mucus plugging ( 82 ). Consequently, thicker and more adherent mucus may create further hypoxic niches within it.…”
Section: Hypoxia-epithelial Interactions: Consequences For the Host Dmentioning
confidence: 99%
“…Mucus hypersecretion may also result in airway obstruction as mucus occupies the airway lumen and inclines to be retained due to ciliary dysfunction [91,92]. Accumulating evidences have been revealed the tremendous complexity of the expression, interactions, and functions of mucins in patients with different severity of COPD, suggesting that modulating the synthesis, secretion, or structure of mucins in these patients might be a useful treatment for this disease [93]. Several natural compounds such as flavonoids have shown their potential effects on the expression and secretion of mucin [94].…”
Section: Expectorantmentioning
confidence: 99%